Analisis Proses Operasional Air Freight Pada Perusahaan Freight Forwarder Menggunakan Value Stream Mapping - Fajar Ciputra Daeng Bani; Muhammad Alde Rizal; Firdhani Faujiyah; Trisna Yuniarti (Politeknik ATI Padang, 2023)
This study aims to provide an overview of the concept of Value Stream Mapping and its significance in process improvement. It highlights the key steps involved in creating a VSM and emphasizes its role in identifying and addressing various types of waste, such as waiting time, unnecessary movement, and rework. By mapping the current state of a process, organizations gain insights into its inefficiencies and areas for improvement. Furthermore, the importance of developing a future state Value Stream Map that outlines the desired state of the process after implementing improvements. It emphasizes the need for continuous monitoring and evaluation to ensure sustained progress and ongoing optimization. Overall, Value Stream Mapping offers organizations a systematic approach to analyze, optimize, and enhance their processes. By visualizing the value flow and identifying opportunities for improvement, businesses can achieve higher levels of efficiency, reduced costs, improved quality, and ultimately deliver greater value to their customers. The calculation and analysis explained that the total processing time was 105.8 minutes and the total lead time was 47 minutes resulting in a non-value added (NVA) of 34 minutes. If the converted into a process percentage form, it is 32% of the total time spent on operational air freight.